EWT framework molecular sieves, methods of manufacture and uses thereof

The aluminum content of EWT skeleton zeolite is increased by repeated treatment method of aluminum brine solution, and the problem of difficult control of the aluminum content of EWT skeleton molecular sieve in the prior art is solved, and the reduction of Si:Al2 ratio and the improvement of material stability are achieved.

CN119255964APending Publication Date: 2025-01-03EXXONMOBIL CHEMICAL PATENTS INC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380042216.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-06
Filing Date
2023-06-26
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

It is difficult to directly synthesize EWT skeleton molecular sieves with the required aluminum content level, especially EMM-23 crystallization with SiO2:Al2O3 ratio less than 100, and the reproducibility and stability of the modified EMM-23 are poor.

Method used

Increase the aluminum content of the EWT skeleton zeolite by repeated treatment with aqueous aluminum salt solution, the specific steps include contacting and separating the zeolite with the aqueous aluminum salt solution, and repeating 2 to 10 treatment cycles to reduce the Si:Al2 ratio to 70 or less .

Benefits of technology

It effectively increases the aluminum content in the EWT framework zeolite, improves the stability and catalytic activity of the material, realizes the reduction of the Si:Al2 ratio, and enhances the reproducibility and application potential of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119255964A_ABST
    Figure CN119255964A_ABST
Patent Text Reader

Abstract

The present disclosure relates to various modified EWT framework zeolites, methods and uses thereof.
Need to check novelty before this filing date? Find Prior Art

Description

CROSS-REFERENCE TO RELATED APPLICATIONS This application claims priority to and the benefit of European application number 22183386.6, filed on July 6, 2022, the entire contents of which are incorporated herein by reference. Technical Field

[0001] The present disclosure relates to EWT framework molecular sieves, methods of making such molecular sieves, and uses of these molecular sieves. More specifically, the present invention relates to methods of increasing the aluminum concentration in EWT framework molecular sieves. Background Art

[0002] EWT framework molecular sieve includes zeolite such as EMM-23. EMM-23 is a crystalline or substantially crystalline material. It is described as a molecular sieve in U.S. Patent No. 9,205,416, the content of which is incorporated herein by reference in its entirety. The framework structure is approved by the Structure Committee of the International Zeolite Association and is described in the Zeolite Structure Database. Molecular sieves can be used as adsorbents, catalysts or carriers of catalysts, particularly for hydrocarbon conversion. EMM-23 has a crystal structure that can be confirmed by X-ray diffraction (XRD) as described in US 9,205,416. EMM-23 has a uniform cavity and pores interconnected by channels. The size and dimensions of the cavity and pore allow molecules of certain sizes to be adsorbed. Due to its ability to select adsorbed molecules via size, EMM-23 has many uses, including hydrocarbon conversion, such as cracking, hydrocracking, disproportionation, alkylation, oligomerization and isomerization.

[0003] EWT framework molecular sieves such as EMM-23 can be prepared from a mixture of source materials of water, hydroxide ions, SiO2, optional Al and a structure directing agent. The structure directing agent can be an organic molecule, such as a diquaternary ammonium molecule. The as-made molecular sieve obtained from these source materials can contain a structure directing agent in the crystalline framework. The thermal treatment (e.g., calcination) of the as-made molecular sieve will produce a molecular sieve without a structure directing agent.

[0004] Including trivalent elements such as aluminum in molecular sieves can lead to modified properties such as increased acidity, which can enhance catalytic activity. It may be difficult to directly synthesize EWT framework molecular sieves with a desired aluminum content level. In particular, it has been proven difficult to crystallize EMM-23 with a framework SiO2:Al2O3 ratio less than 100. Although EMM-23 has been previously described in U.S. Patent No. 9,205,416, and methods for modifying EMM-23 are described in US 2019 / 0030518 A1 and US 2019 / 0031519 A1, there is still a need for modified materials of EMM-23 with improved properties. Summary of the invention SUMMARY OF THE INVENTION

[0005] The present disclosure provides an improved process for preparing EWT framework zeolites having increased aluminum content. More particularly, the present invention relates to a process wherein the aluminum content of an EWT zeolite is increased by repeated treatment with an aqueous solution of an aluminum salt.

[0006] In a first aspect, the present invention provides a method of increasing the aluminium content of an EWT framework zeolite and mixtures thereof, the method comprising subjecting the EWT framework zeolite to a treatment comprising the steps of: a) contacting the EWT framework zeolite with an aqueous solution of an aluminum salt; and b) separating the EWT framework zeolite from the aqueous solution of the aluminum salt; and repeating the treatment such that the EWT framework zeolite is subjected to n treatment cycles in total, wherein n is a number from 2 to 10.

[0007] The inventors have found that the process of the first aspect of the invention is unexpectedly effective in incorporating aluminium into an EWT framework zeolite, thereby enabling the provision of an EWT framework zeolite having a Si:Al2 ratio of 70 or less.

[0008] In a second aspect, the present invention provides an EWT framework zeolite produced by the method according to the first aspect, wherein the Si:Al2 ratio is 70 or less.

[0009] In a third aspect, the present invention provides a method of converting an organic compound into a conversion product, comprising the step of contacting the organic compound with the EWT framework zeolite according to the second aspect.

[0010] EMM-23 is the preferred EWT framework zeolite.

[0011] As used herein, SiO2:Al2O3 ratio and Si:Al2 ratio have the same meaning and are molar ratios.

[0012] Any two or more features described in this specification (including in the Summary of the Invention) may be combined to form a combination of features not specifically described herein. The details of one or more features are described in the accompanying drawings and the following description. Other features and advantages will be apparent from the specification and drawings and claims. Description of the drawings

[0013] Figure 1 The powder XRD pattern of the as-received EMM-23 prepared in Example 1 is shown.

[0014] Figure 2 The as-received EMM-23 prepared in Example 1 is shown. 27 Al MAS NMR spectrum.

[0015] Figure 3 The powder XRD pattern of calcined EMM-23 prepared in Example 2 is shown.

[0016] Figure 4 The calcined EMM-23 prepared in Example 2 is shown. 27 Al MAS NMR spectrum.

[0017] Figure 5 The powder XRD pattern of the treated EMM-23 prepared in Example 3 is shown.

[0018] Figure 6 The powder XRD pattern of treated EMM-23 prepared in Example 4 is shown.

[0019] Figure 7 The powder XRD pattern of treated EMM-23 prepared in Example 5 is shown.

[0020] Figure 8 The powder XRD pattern of the treated EMM-23 prepared in Example 6 is shown.

[0021] Fig. 9 The powder XRD pattern of the treated EMM-23 prepared in Example 7 is shown.

[0022] Fig.10 The calcined EMM-23 prepared in Example 2 and the treated EMM-23 prepared in Examples 7 to 12 are shown. 27 Al MAS NMR spectrum.

[0023] Fig.11 A shows the overlaid powder XRD patterns of calcined EMM-23 of Examples 2, 3, 6 to 13, and 15.

[0024] Fig.11 B shows the overlaid powder XRD patterns of the as-received EMM-23 of Examples 1, 4, 5, 14 and 16. DETAILED DESCRIPTION OF THE INVENTION

[0025] Provided herein are various modified EWT framework zeolites, methods for preparing these zeolites, and uses thereof. The EWT framework zeolite as is (i.e., before heat treatment or other treatment to remove the structure directing agent (SDA), which may be referred to herein as "as synthesized" or "as is") may include a structure directing agent (SDA) as one of the synthetic reagents. Heat treatment (e.g., calcination) of EMM-23 as is typically performed by exposing the material to a high temperature, e.g., 400-600°C, in an atmosphere selected from air, nitrogen, or a mixture thereof to remove the SDA. The heat treated (e.g., calcined) form of the EWT framework zeolite may be described as a chemical composition having an oxide of a trivalent element (e.g., Al2O3) and an oxide of a tetravalent element (e.g., SiO2), wherein these oxides may be in various molar ratios.

[0026] The concentration of aluminum in a zeolite is usually expressed as the molar ratio of silicon dioxide to aluminum oxide, i.e., the ratio of SiO2:Al2O3. This is usually abbreviated as the Si:Al2 ratio, and for the purposes of this disclosure, the expressions Si:Al2 and SiO2:Al2O3 should be considered equivalent. Sometimes, the concentration of aluminum in a zeolite is expressed as the ratio of silicon atoms to aluminum atoms, i.e., Si:Al. The ratio expressed as Si:Al will be numerically half of the ratio expressed as Si:Al2. For example, a ratio Si:Al=75 corresponds to a Si:Al2 of 150. Additional aluminum bonding

[0027] Additional modified EWT framework zeolites are provided herein, which contain a larger amount of aluminum. The modified EWT framework zeolite with more aluminum is more stable during heat treatment (e.g., calcination) or in its final heat-treated form than the material with less aluminum. It may be difficult to prepare an EWT framework zeolite, such as EMM-23 zeolite, with an atomic ratio of Si to Al less than 75 (e.g., Si:Al less than 75, equivalent to Si:Al2 less than 150). A possible approach to incorporating more aluminum into the EWT framework zeolite is to prepare the EWT framework zeolite as is by increasing the amount of aluminum source material (one or more) in the mixture. However, in practice, this method does not incorporate a large amount of additional aluminum into the EWT framework zeolite, and the reproducibility of the synthesis seems to be sensitive to the presence of aluminum and may cause undesirable impurities. Described herein is an aluminum-modified EWT framework zeolite with a Si:Al2 molar ratio less than 70 prepared by the following method, the method comprising incorporating Al into the EWT framework zeolite (i.e., the EWT framework zeolite already prepared) by repeated treatment cycles with an aluminum salt aqueous solution.

[0028] In the method of the first aspect of the invention, steps a) and b) are performed in the order described. A single performance of those steps a) and b) constitutes a treatment cycle. If these steps are performed only once, there is only one treatment cycle and n=1. The inventors have found that the amount of additional aluminum incorporated in the zeolite tends to decrease with increasing number of cycles. In the method of the invention, the treatment cycle is performed for the first time and then repeated at least once and not more than nine times, so that the total number of treatment cycles n is in the range of 2 to 10. Optionally, n is in the range of 2 to 8, optionally 3 to 6.

[0029] In step a), the contact time of the EWT framework zeolite with the aqueous solution of the aluminum salt can be any suitable duration. Optionally, in step a), the EWT framework zeolite is contacted with the aqueous solution of the aluminum salt for a duration of 0.25 hours to 24 hours, optionally 1 hour to 24 hours, optionally 2 hours to 6 hours.

[0030] Any aluminum salt that is at least partially soluble in water can be used for the treatment. Preferably, the aluminum salt is soluble in water to at least 0.05 wt. %, preferably at least 0.1 wt. % at 25° C. Suitable salts can be selected from Al(NO 3 ) 3 , Al 2 (SO 4 ) 3 , AlCl 3 , (NH 4 ) 3 AlF 6 or mixtures thereof. For example, the aluminum salt can include or be Al(NO 3 ) 3 .

[0031] Each treatment cycle of the method of the first aspect of the present invention may independently and optionally include one or more additional steps. Optionally, in one or more of the treatment cycles, the treatment further includes the following steps after step b): c) washing the EWT framework zeolite with a wash liquid. Optionally, in all treatment cycles, the treatment further includes the following steps after step b): c) washing the EWT framework zeolite with a wash liquid.

[0032] Typically, the washing liquid will be an aqueous liquid. For example, the washing liquid may be water, particularly water having a pH of 6.0 to 8.0. The washing liquid may suitably be selected from distilled water and deionized water. Alternatively, the washing liquid may be an alkaline aqueous solution, such as an aqueous solution of ammonium hydroxide or an aqueous solution of, for example, an alkali metal or alkaline earth metal hydroxide (subsequently exchanging the alkali metal or alkaline earth metal(s) with ammonium ions, including, for example, NH4 +, tetraalkylammonium such as tetramethylammonium, tetraethylammonium, tetrapropylammonium and so-called diquaternary ammonium (diquat), such as C3, C4, C5 or C6 diquaternary ammonium), preferably aqueous ammonium hydroxide solution. The use of alkaline washing solutions such as aqueous ammonium hydroxide solution promotes the removal of octahedral coordinated aluminum, and its removal can produce greater selectivity in any reaction in which the zeolite is used as a catalyst. However, contact with alkaline solutions also tends to reduce the crystallinity of the zeolite, so the pH of the alkaline washing solution and the duration and conditions of the washing steps must be selected to avoid excessive degradation of the crystalline structure. In the case where more than one treatment cycle includes a washing step c), different washing solutions can be used in different cycles. For example, some treatment cycles can use neutral water with a pH of 6.0 to 8.0, while other treatment cycles can use alkaline washing solutions, such as aqueous ammonium hydroxide solution. Optionally, at least one treatment cycle includes a washing step c), wherein the washing solution is alkaline, such as aqueous ammonium hydroxide solution.

[0033] The separation step b) may comprise separating the EWT framework zeolite from the aqueous solution of aluminium salt by any suitable technique. For example, the separation may comprise filtration or centrifugation. The separation step b) will typically remove at least 90% by weight of the aqueous solution of aluminium salt, and will preferably remove substantially all of the aqueous solution of aluminium salt to leave the zeolite as a wet solid. As described above, the wet solid may then be subjected to an optional washing step c). Optionally, the wet solid may be subjected to an optional step d of drying the EWT framework zeolite. The drying step d) may be carried out directly after step b) if there is no washing step c), or directly after the washing step c) if there is a washing step c).

[0034] The optional drying step d) may comprise contact with hot air, for example at a temperature of 40 to 200° C., optionally 50 to 100° C. The duration of the drying step may optionally be 1 to 24 hours, for example 3 to 12 hours.

[0035] Typically, the final processing cycle will comprise a drying step d) to leave the zeolite as a dry zeolite at the end of the process. Optionally, only the final processing cycle comprises a drying step d).

[0036] The contacting step a) can be carried out in any suitable container. For example, step a) can be carried out as a batch process in a stirred tank reactor. Advantageously, step a) is carried out at a temperature above 40°C, preferably at a temperature of 50°C to 100°C, more preferably at a temperature of 60°C to 95°C. Although step a) can be carried out under high pressure, such as in an autoclave, to raise the temperature to above 100°C, it is generally convenient to carry out step a) at atmospheric ambient pressure.

[0037] Optionally, the EWT framework zeolite is an uncalcined or "as is" EWT framework zeolite. Such an uncalcined or "as is" zeolite will typically contain a certain amount of structure directing agent (SDA) within its pore structure. If the EWT framework zeolite is an uncalcined or "as is" EWT framework zeolite, the method of the present invention may include a step of calcining the zeolite after the final treatment cycle to remove the SDA. Alternatively, the EWT framework zeolite used in the method of the first aspect of the present invention is a calcined EWT framework zeolite.

[0038] Preferably, the EWT framework zeolite is EMM-23, and optionally calcined EMM-23.

[0039] The EWT framework zeolite used in the method of the first aspect of the invention may be in any suitable form. For example, the EWT framework zeolite may be in the form of unbound zeolite crystals. Alternatively, the EWT framework zeolite may be in the form of pellets or granules comprising a binder.

[0040] As described above, in a second aspect, the present invention provides an EWT framework zeolite produced by a method according to the first aspect, wherein the Si:Al2 ratio is 70 or less. Optionally, the Si:Al2 ratio is 60 or less, optionally 55 or less. Optionally, the Si:Al2 ratio is at least 15, optionally at least 20. The Si:Al2 ratio may be from 15 to 70, for example from 20 to 60.

[0041] As also described above, in a third aspect, the present invention provides a method of converting an organic compound into a conversion product, comprising the step of contacting the organic compound with an EWT framework zeolite according to the second aspect. Preferably, the EWT framework zeolite according to the second aspect of the present invention is EMM-23.

[0042] The EMM-23 used in the method of the first aspect of the invention can be substantially free of one or more impurities (e.g., at least 50 wt%, at least 60 wt%, at least 70 wt%, at least 80 wt%, at least 90 wt%, at least 95 wt%, at least 97 wt%, or at least 99 wt% of the EMM-23 is free of impurities (i.e., the weight percentages are based on the total weight of the material that is EMM-23 but not the impurities)), such as zeolite beta, ZSM-5, or a mixture thereof. The EMM-23 used in the method can be substantially free of one or more impurities, such that other phases, such as zeolite beta, ZSM-5, or a mixture thereof, cannot be identified in the XRD pattern of the modified EMM-23 material.

[0043] EMM-23 may have an alpha value greater than 10. The alpha value of EMM-23 may be greater than 20, greater than 30, greater than 40, or greater than 50. In some examples, the alpha value may be 15-50, 20-40, or 30-35.

[0044] EMM-23 may have a micropore volume greater than 0.15 cc / g. The micropore volume may be from 0.15 to 0.30, 0.25 to 0.30 cc / g, or 0.20 to 0.30 cc / g. ... The a-parameters of a cell and The c-parameter.

[0045] EMM-23 optionally has at least four XRD peaks having 2θ values ​​(degrees) selected from Table 1: Table 1

[0046] EMM-23 optionally has at least four XRD peaks having 2θ (degrees) and d-spacing values ​​selected from Table 2, wherein when converted to corresponding d-spacing values ​​using Bragg's law, the d-spacing values ​​have deviations determined based on corresponding deviations ±0.20 2θ (degrees). Table 2

[0047] Optionally, EMM-23 has at least five or six XRD peaks selected from Table 1 or Table 2. EMM-23 may have at least four, at least five, or six XRD peaks having 2θ values ​​selected from Table 1 or 2 and a micropore volume greater than 0.15 cc / g (e.g., 0.15 to 0.30, 0.25 to 0.30 cc / g, or 0.20 to 0.30 cc / g), or The a-parameters of the unit cell and The c-parameter.

[0048] Optionally, EMM-23 has at least four XRD peaks having 2θ values ​​(degrees) selected from Table 3: Table 3

[0049] Optionally, EMM-23 has at least four XRD peaks having 2θ (degrees) and d-spacing values ​​selected from Table 4, wherein when converted to corresponding d-spacing values ​​using Bragg's law, the d-spacing values ​​have deviations determined based on corresponding deviations ±0.20 2θ (degrees). Table 4

[0050] Optionally, EMM-23 has at least five, at least six, at least seven, at least eight, at least nine, or ten XRD peaks having 2θ values ​​(degrees) selected from Table 3 or Table 4. EMM-23 may have at least four, at least five, at least six, at least seven, at least eight, at least nine, or ten XRD peaks having 2θ values ​​(degrees) selected from Table 3 or Table 4 and a micropore volume greater than 0.15 cc / g (e.g., 0.15 to 0.30, 0.25 to 0.30 cc / g, or 0.20 to 0.30 cc / g), or The unit cell a-parameter and The c-parameter.

[0051] EMM-23 optionally has at least four XRD peaks having 2θ values ​​(degrees) selected from Table 5: Table 5

[0052] EMM-23 optionally has at least four XRD peaks having 2θ (degrees) and d-spacing values ​​selected from Table 6, wherein when converted to corresponding d-spacing values ​​using Bragg's law, the d-spacing values ​​have deviations determined based on corresponding deviations ±0.20 2θ (degrees). Table 6

[0053] EMM-23 optionally has at least five, at least six, at least seven, at least eight, at least nine, at least ten, at least eleven, or twelve XRD peaks having 2θ values ​​(degrees) selected from Table 5 or Table 6. EMM-23 optionally has at least four, at least five, at least six, at least seven, at least eight, at least nine, at least ten, at least eleven, or twelve XRD peaks having 2θ values ​​(degrees) selected from Table 5 or Table 6 and a micropore volume greater than 0.15 cc / g (e.g., 0.15 to 0.30, 0.25 to 0.30 cc / g, or 0.20 to 0.30 cc / g), or The unit cell a-parameter and For the avoidance of doubt, the XRD peaks of EMM-23 of the present invention may have intensities different from those listed in Tables 1 to 6 above.

[0054] As described above, in a second aspect, the present invention provides an EWT framework zeolite produced by a method according to the first aspect, wherein the Si:Al2 ratio is 70 or less. Optionally, the Si:Al2 ratio is 60 or less, optionally 55 or less. Optionally, the Si:Al2 ratio is at least 15, optionally at least 20. The Si:Al2 ratio can be from 15 to 70, for example 20 to 60. In a preferred embodiment, the EWT framework zeolite according to the second aspect of the present invention is EMM-23. The EMM-23 according to the second aspect of the present invention will have a modified XRD pattern, but many XRD peaks may optionally be retained, which have the same 2θ (degrees) and / or d-spacing values ​​as described above for the EMM-23 used in the method of the first aspect with reference to Tables 1 to 6. Preparation of EMM-23

[0055] EMM-23 as received (eg, material prior to heat treatment to remove SDA) can be prepared from a mixture of sources of water, hydroxide ions, Si, optionally Al, and optionally the structure directing agent SDA.

[0056] For example, the molar ratios in the mixture may be as follows: SiO2 / Al2O3 may be at least 5 (e.g., at least 100, at least 1000, or all SiO2); H2O / SiO2 may be 0.5 to 50 (e.g., 2 to 10 or 14 to 40); OH- / SiO2 may be 0.1 to 1.0 (e.g., 0.2 to 0.5); and SDA / SiO2 may be 0.05 to 0.5 (eg, 0.1 to 0.25).

[0057] In one or more aspects, the molar ratios of these source materials in the as-received EMM-23 (which is subsequently heat treated to produce calcined EMM-23) can be as follows: SiO2 / Al2O3 may be equal to or at least 75 (e.g., at least 100, at least 1000, or all SiO2); H2O / SiO2 may be 0.5 to 50 (e.g., 2 to 10 or 14 to 40); OH- / SiO2 may be 0.1 to 1.0 (e.g., 0.2 to 0.5); and SDA / SiO2 may be 0.05 to 0.5 (eg, 0.1 to 0.25).

[0058] In one or more aspects, the EMM-23 material as is can be prepared as follows: the source material of Al is mixed with the hydroxide solution of SDA, and then the source material of Si is added to the mixture to form the basic mixture of each component. The seed of EMM-23 material can be added to the basic mixture. The solvent (for example, water from the hydroxide solution, and optionally, methanol and ethanol from the hydrolysis of the silicon dioxide source material) of the basic mixture can be removed (for example, by evaporation or freeze drying) so that the resulting mixture reaches the desired solvent and SiO2 molar ratio. When too much water is removed in the solvent removal process, water can be added to the resulting mixture to achieve the desired H2O / SiO2 molar ratio. The mixture is then sealed in a suitable reaction vessel, for example, sealed in a steel Paar autoclave. Optionally, the sealed mixture is heated under tumbling or stirring so that the sealed mixture is kept at a certain temperature for a period of time (for example, kept in a sealed autoclave placed in a convection oven kept at 150°C for 1 day to 14 days) enough to form EMM-23 crystals. Detailed procedures for preparing as-received EMM-23 material can also be found in US Pat. No. 9,205,416, which is incorporated herein by reference in its entirety.

[0059] Examples of Si source materials may be selected from colloidal suspensions of silica, precipitated silica, fumed silica, alkali metal silicates and / or tetraalkyl orthosilicates (e.g., tetraethyl orthosilicate, tetramethyl orthosilicate, etc.). Examples of different silica source materials may include (For example AS-40) colloidal silica, precipitated silica e.g. Products and Products, CARBOSPERSE TM Fumed silica suspensions and Fumed silica or mixtures thereof.

[0060] The Al source may include or may be aluminum, and other suitable aluminum sources may be selected from hydrated aluminum oxide, aluminum hydroxide, alkali metal aluminates, aluminum alkoxides, and water-soluble aluminum salts, such as aluminum nitrate. Suitable sources of structure directing agents may be selected from hydroxides and / or salts of relevant diquaternary ammonium compounds, such as 1,5-bis(n-propylpyrrolidone) )pentane dication, 1,6-bis(n-propylpyrrolidine ) hexane dication, 1,4-bis(n-methylpyrrolidine )Butane dication.

[0061] In one or more aspects, the solvent adjusted mixture (e.g., wherein the desired water to silica molar ratio is achieved) can be mixed by mechanical methods, such as stirring or high shear blending, to ensure suitable homogenization of the base mixture. For example, the use of a FlackTek speed mixer with a mixing speed of 1800 to 2200 rpm (e.g., 2000 rpm) can improve the homogenization of the base mixture. Depending on the nature of the reagents in the base mixture, the amount of solvent (e.g., water) in the mixture can be reduced prior to crystallization to obtain the desired solvent molar ratio (e.g., H2O / SiO2). Suitable methods for reducing the solvent (e.g., water) content can include evaporation under a static or flowing atmosphere such as ambient air, dry nitrogen, dry air, or by spray drying or freeze drying. In one or more aspects, the use of a silica source such as (For example AS-40), CARBOSPERSE TM Or a mixture thereof, with a mixing speed of 1800 to 2200 rpm (e.g., 2000 rpm), a base mixture having a desired solvent molar ratio (e.g., H2O / SiO2 molar ratio) can be produced without removing the solvent from the base mixture. Even when the mixture has a solvent molar ratio (e.g., H2O / SiO2 molar ratio) greater than 10 (e.g., 15 to 40), a high mixing speed such as 2000 rpm can produce homogenization of the mixture.

[0062] Crystallization of EMM-23 in the formation of as-received EMM-23 can be carried out under static or stirred conditions in a suitable reactor vessel, such as a polypropylene can or a Teflon-lined or stainless steel autoclave, which is placed in a convection oven maintained at a temperature of about 100 to about 200° C. for a period of time sufficient for crystallization to occur at the temperature used, such as about 1 day to about 14 days. Thereafter, the solid crystals of as-received EMM-23 are separated from the liquid (e.g., by filtration or centrifugation) and recovered.

[0063] Part or all of SDA can be removed to form calcined EMM-23 when used during the synthesis of EMM-23 as is. The removal of SDA can be carried out using heat treatment (e.g., calcination), wherein the EMM-23 material as is is heated at a temperature sufficient to remove part or all of SDA in an atmosphere selected from air, nitrogen, or its mixture. Although heat treatment can be carried out using a pressure lower than atmospheric pressure, for convenience, atmospheric pressure is desired. Heat treatment can be carried out at a temperature of up to 650°C, such as 400-600°C. Heat treatment (e.g., calcination) can be carried out in a box furnace in dry air, and the dry air has been exposed to a drying tube containing a desiccant for removing water from the air. Heat-treated EMM-23 materials (e.g., calcined products) can be used for catalyzing some organic (e.g., hydrocarbon) conversion reactions.

[0064] EWT framework zeolite (e.g., EWT framework zeolite as is, calcined, modified, unmodified or in any other form) can be combined with a hydrogenation component. The hydrogenation component can be selected from molybdenum, tungsten, rhenium, nickel, cobalt, chromium, manganese or a precious metal, such as platinum or palladium, in which the hydrogenation-dehydrogenation function is to be performed. Such hydrogenation components can be incorporated into the composition by one or more of the following methods: co-crystallization; exchange into the composition to the extent that the Group IIIA element (e.g., aluminum) is in the structure; impregnation therein; or physical admixture therewith. For example, such hydrogenation components can be impregnated into the EWT framework zeolite. In the case of platinum, the EWT framework zeolite can be impregnated with a solution containing ions of a platinum-containing metal. Suitable platinum compounds for impregnation can be selected from chloroplatinic acid, platinous chloride and compounds containing platinum amine complexes. A combination of all of the above, such as the use of heating and vacuum, is an effective method for at least partially dehydrating the EWT framework zeolite.

[0065] When used as an adsorbent or catalyst, the EWT framework zeolite (e.g., as is, calcined, modified, unmodified, or any other form of EWT framework zeolite) can be at least partially dehydrated. This dehydration can be achieved by heating EMM-23 at a temperature of 200 to 370° C. in an ambient atmosphere for 30 minutes to 48 hours, the atmosphere being selected from air, nitrogen, or a mixture thereof, and at atmospheric pressure, subatmospheric pressure, or superatmospheric pressure. Dehydration can also be carried out at room temperature by placing the EWT framework zeolite in a vacuum; however, a longer time is required to obtain a sufficient amount of dehydration. A combination of all of the above, such as the use of heating and vacuum, is an effective method for at least partially dehydrating the EWT framework zeolite.

[0066] As described above, in a third aspect, the present invention provides a method for converting an organic compound into a conversion product, which comprises the step of contacting the organic compound with the EWT framework zeolite according to the second aspect.

[0067] EWT framework zeolite, such as EMM-23 (e.g., EWT framework zeolite as is, calcined, modified, unmodified or in any other form) can be used as an adsorbent or as a catalyst in the form of aluminosilicate to catalyze various organic compound conversion processes. Examples of chemical conversion processes effectively catalyzed by the treated EWT framework zeolite of the second aspect of the present invention alone or in combination with one or more other catalytically active substances (including other crystalline catalysts) include those requiring a catalyst with acid activity. Examples of organic conversion processes that can be catalyzed by the EWT framework zeolite of the second aspect of the present invention include cracking, hydrocracking, disproportionation, alkylation, oligomerization and isomerization.

[0068] EWT framework zeolite (e.g., as is, calcined, modified, unmodified or any other form of EWT framework zeolite) can be combined with other materials that tolerate the temperature and other conditions used in organic conversion processes. Such tolerant materials can be selected from active materials, inactive materials, synthetic zeolites, naturally occurring zeolites, inorganic materials or mixtures thereof. Examples of such tolerant materials can be selected from clays, silica, metal oxides such as alumina or mixtures thereof. The inorganic material can be naturally occurring or in the form of a gelatinous precipitate or gel including a mixture of silica and metal oxides. Tolerant materials are used in combination with EWT framework zeolite, i.e., combined with it or present during the synthesis of as is zeolite crystals (the crystals are active), tending to change the conversion rate and / or selectivity of the catalyst in certain organic conversion processes. In addition, inactive tolerant materials suitably act as diluents to control the amount of conversion in a given process so that the product can be obtained in an economical and orderly manner without the need to adopt other means of controlling the reaction rate. These materials can be incorporated into naturally occurring clays, such as bentonite and kaolin, to improve the crushing strength of the catalyst under commercial operating conditions. The inactive resistant material, ie clay, oxide, etc., acts as a binder for the catalyst.A catalyst having good crush strength may be beneficial because in commercial use it is desirable to prevent the catalyst from decomposing into a powdery material.

[0069] Naturally occurring clays that can be composited with EWT framework zeolites such as EMM-23 include the montmorillonite and kaolin families, which include subbentonites and kaolins commonly known as Dixie, McNamee, Georgia and Florida clays or other clays in which the main mineral components are halloysite, kaolinite, dickite, nacrite or anthracite. Such clays can be used in their original state as originally mined or initially subjected to calcination, acid treatment or chemical modification. Binders that can be used to composite with EWT framework zeolites such as EMM-23 also include inorganic oxides selected from silica, zirconium oxide, titanium oxide, magnesium oxide, beryllium oxide, aluminum oxide or mixtures thereof.

[0070] EWT framework zeolite (e.g., EWT framework zeolite as is, calcined, modified, unmodified or in any other form) can be composited with porous matrix materials such as silica-alumina, silica-magnesia, silica-zirconia, silica-thoria, silica-beryllia, silica-titania, and ternary compositions such as silica-alumina-thoria, silica-alumina-zirconia, silica-alumina-magnesia and silica-magnesia-zirconia.

[0071] The relative proportions of the EWT framework zeolite and the inorganic oxide matrix may vary widely, with the EWT framework zeolite content being from about 1 to about 90 weight percent of the composite or from about 2 to about 80 weight percent of the composite when the composite is prepared in bead form.

[0072] In one or more aspects, embodiments described herein using the language "a material comprising" with respect to a particular composition are meant to include "a material comprising or being the particular composition."

[0073] As used herein and unless otherwise indicated, numerical values ​​or ranges of values ​​may deviate from what is considered reasonable by a person of ordinary skill in the relevant art. It is well known that instrument variations and other factors may affect numerical values. Unless otherwise specified, such deviations may be plus or minus 2%, 5%, 10%, 15%, 20%, 25%, or 30% of the numerical values ​​or ranges of values ​​shown.

[0074] As used herein, the term "substantially free" means that the material described herein (e.g., EWT framework zeolite) is at least 50 wt%, at least 60 wt%, at least 70 wt%, at least 80 wt%, at least 90 wt%, at least 95 wt%, at least 97 wt%, or at least 99 wt% (e.g., 99.5 wt% or 99.9 wt%) pure EWT framework zeolite material, based on the total weight of the composition, as determined by quantification using XRD or NMR spectra (e.g., by measuring the area or relative intensity of the relevant peaks), or by other known methods suitable for such determination. The remainder of the material is non-EWT framework zeolite material, which may be structure directing agent, amorphous material, other impurities, or mixtures thereof.

[0075] The term "crystallization" as used herein refers to the crystalline solid form of a material, including but not limited to single-component or multi-component crystal forms, such as solvates, hydrates, and eutectics. Crystallization can mean molecules with regular repetition and / or orderly arrangement, and with distinguishable lattices. For example, the EMM-23 of crystallization can have different water or solvent contents. Different lattices can be identified by solid-state characterization methods such as by XRD (for example, powder XRD). Other characterization methods known to those of ordinary skill in the relevant art can further help identify crystalline forms and help determine stability and solvent / water content.

[0076] As used herein, the term "substantially crystalline" means that a majority (greater than 50%) of the weight of a sample of the solid material is crystalline, and the remainder of the sample is in a non-crystalline form. In one or more aspects, a substantially crystalline sample has at least 95% crystallinity (e.g., 5% non-crystalline form), at least 96% crystallinity (e.g., 4% non-crystalline form), at least 97% crystallinity (e.g., 3% non-crystalline form), at least 98% crystallinity (e.g., about 2% non-crystalline form), at least 99% crystallinity (e.g., 1% non-crystalline form), and 100% crystallinity (e.g., 0% non-crystalline form). Analytical methods

[0077] Inductively coupled plasma (ICP) analysis combined with mass spectrometry (ICP-MS) technique was used to evaluate the elemental composition of the samples. First, 50 mg of the sample was digested with a mixture of aqua regia (a mixture of HCl and HNO3) and HF in a closed PTEF container at 90°C. The mixture was then neutralized by adding H3BO4. The obtained solution was concentrated at 1000 cm 3 A metered volume of analyte is diluted, nebulized / ionized using a high energy Ar-plasma and then accelerated in a mass spectrometer to allow acquisition of a mass spectrum of the analyte solution.

[0078] Solid-state NMR measurements were recorded on a Bruker Avance 500 spectrometer with a 4-OD mm zirconia rotor and a 14 kHz rotation speed. The zeolite samples were obtained using a short quantitative single pulse (π / 12) at 130.3 MHz, a recycle delay of 1 s, and 1856 scans. 27 Al MAS NMR spectra. A 1.0 M aqueous solution of Al(NO3)3 was used as an external reference (0 ppm). The spectra were normalized to 100 mg of hydrated material.

[0079] Acidity - Pyridine adsorption was used to assess the acidity of the samples. This study was performed using a standard in situ Fourier transform infrared (FTIR) setup. The samples were analyzed at 4 cm on a Nicolet Magna 550 FTIR spectrometer equipped with a DTGS detector. -1Infrared spectra were recorded at optical resolution with first-order zero-filling for the Fourier transform. Prior to the measurements, the samples were ground and pressed into self-supporting disks (2 cm diameter, approximately 5 mg cm -2 ) and in vacuum (about 10 -6 hPa) at 450 °C for 4 h (2 °C min -1 ). After cooling to room temperature, the sample spectrum was recorded as a reference. Then, a saturation pressure of the probe molecule (1 Torr of pyridine) was established in the chamber at ambient temperature to reach saturation. The wafer was heated at 150°C for 30 minutes to promote the diffusion of the probe molecules into the sample. Continuous evacuation was performed at room temperature, 150°C, 200°C, 250°C, 300°C and 350°C at intervals of 15 minutes. All spectra were normalized to 20 mg of dehydrated zeolite. The amount of Lewis sites (L) and Bronsted (B) sites was measured using the coordinated pyridine at 1450 cm -1 The band area and adsorbed pyridine At 1545cm -1 The molar extinction coefficients (ε) used for quantification were taken from Guisnet et al.: ε1545 (B-pyridine) = 1.13 cm μmol-1 and ε1455 (L-pyridine) = 1.28 cm μmol-1. The OMNIC version 7.3 SP1 program was used for data processing.

[0080] The term "α value" as used herein refers to the catalytic activity of a material (e.g., the EWT framework zeolite described herein), which is measured by the ratio of the rate constant of a test sample for cracking n-hexane to the rate constant of a standard reference catalyst, which is optionally an amorphous silica / alumina. See, for example, PB Weisz and JN Miale, J. Catalysis, 4 (1965) 527-529; and JN Miale, NY Chen and PB Weisz, J. Catalysis, 6 (1966) 278-287. For example, an α value of 1 means that the test sample and the reference standard sample have approximately the same activity. In one or more aspects, the treated EWT framework zeolite according to the second aspect of the invention may have an α value greater than 10.

[0081] The micropore volume of the modified EWT framework zeolite described herein can be determined using methods known in the relevant art. For example, the material can be measured using nitrogen physical adsorption, and the data can be analyzed by the t-plotting method described in Lippens, BC et al., "Studies on pore systems in catalysts: V. The t method", J. Catal., 4, 319 (1965), which describes the micropore volume method and is incorporated herein by reference. Using this nitrogen physical adsorption method, the treated EWT framework zeolite of the second aspect of the present invention can have a micropore volume of 0.15 to 0.30, 0.25 to 0.30cc / g or 0.20 to 0.30cc / g.

[0082] The X-ray diffraction data reported in this paper were obtained by powder X-ray diffraction (PXRD) using Cu Kα radiation with an average PANalytical X'Pert Pro diffractometer is collected. Use θ-2θ scanning within the range of 3-50 ° 2θ and 0.02 ° step length. The instrument is calibrated on LaB6 srm660b standard powder from the National Institute of Standards and Technology for the contribution of line broadening. Interplanar spacing (d-spacing) is calculated in angstroms, and the relative intensity I / Io of the line is the ratio of the peak intensity to the intensity of the strongest line above the background. For Lorentz and polarization effects, the intensity is not corrected. Interplanar spacing (d-spacing) is calculated in angstroms, and the relative peak area intensity I / I (o) of the line is one percent of the intensity of the strongest line above the background, measured with the MDI Jade peak profile fitting algorithm. It should be understood that the diffraction data listed as a single line can be composed of multiple overlapping lines, which can be expressed as split or partially split lines under certain conditions, such as differences in crystallographic changes. Typically, crystallographic changes can include small changes in unit cell parameters and / or changes in crystal symmetry, while the structure does not change. These minor effects (including relative intensity variations) may also occur due to differences in cation content, framework composition, nature and extent of pore filling, crystal size and shape, preferred orientation, and thermal and / or hydrothermal history.

[0083] Various aspects of the present disclosure are described in more detail by specific examples. The following examples are provided for illustrative purposes and are not intended to limit the present disclosure in any way. Those skilled in the relevant art will readily recognize that various parameters can be changed or modified to produce substantially the same results. Example

[0084] Hereinafter, Examples 1 and 2 are reference examples disclosing the preparation of as-received and calcined EMM-23, respectively. Examples 3, 6, 7, 13 and 15 are reference examples disclosing a single treatment of calcined EMM-23 with a solution comprising an aluminum salt. Examples 4, 5, 14 and 16 are reference examples disclosing a single treatment of as-received EMM-23 with a solution comprising an aluminum salt. Examples 8 to 12 are in accordance with the present invention and disclose repeated treatments of calcined EMM-23 with a solution comprising an aluminum salt. Example 1 - Hydrothermal Synthesis of EMM-23 as received

[0085] 37.3 g of 15% aluminum nitrate solution was dissolved in 1211.5 g of 22.4 wt% 1,1-(pentane-1,5-diyl)bis(1-propylpyrrolidine hydroxide) ). 1.9 g EMM-23 seeds were added to the aluminate solution and stirred until the seeds were evenly distributed. Under vigorous stirring, 499.0 g tetramethyl orthosilicate (TMOS) was slowly added to the aluminate solution containing the seeds. The mixture was stirred for 30 minutes to completely hydrolyze the TMOS. In order to obtain the appropriate H2O / SiO2 ratio, the weight of the mixture was reduced to 765.3 g by heating at 75°C in a forced air drying oven. The mixture was transferred to a 2L stirred autoclave. While stirring at 250 rpm, the mixture was heated to 150°C. After the slurry was reacted at 150°C for 120 hours, the resulting crystalline product was separated from any liquid via vacuum filtration and washed with three reactor volumes of water. After drying on the vacuum filter, the wet cake was dried at 120°C for 16 hours to produce a dry cake. Powder XRD (see Figure 1 ) and elemental analysis via AA / ICP indicated that the resulting material was EMM-23 with a Si:Al2 ratio of approximately 400. Figure 2 The as-received EMM-23 prepared in Example 1 is shown. 27 Al MAS NMR spectrum. Example 2 - Calcination of As-Received EMM-23 from Example 1

[0086] The original EMM-23 sample of Example 1 was heated in a muffle furnace at 4 °C min -1 The heating rate is 100 cm 3 min -1 Heating was performed from ambient temperature to 400° C. under nitrogen flow. Then, the nitrogen was gradually switched to air while the temperature was increased to 540° C. using the same heating rate and maintained at 540° C. for 2 hours under air flow. Figure 3 shows the powder XRD pattern of calcined EMM-23 prepared in Example 2, Figure 4 It shows its 27Al MAS NMR spectrum. Example 3 - Treatment of calcined EMM-23 with AlCl3·6H2O

[0087] The sample of calcined EMM-23 of Example 2 was subsequently subjected to post-synthesis alumination. Post-synthesis alumination was performed with a 0.4 wt% AlCl3·6H2O solution at a solid-to-liquid ratio of 1:50. The mixture was stirred overnight at 80°C with a stirring speed of 400 rpm. After treatment, the sample was purified by a series of high-speed centrifugation / decantation of the supernatant and redispersion of the sample under ultrasonic treatment (UT) according to the following protocol: 1) centrifugation / decantation at 20000 rpm for 20 minutes; 2) washing with water, redispersion under ultrasonic treatment (UT) for 10 minutes, centrifugation / decantation at 20000 rpm for 20 minutes; 3) washing with 0.1M NH4OH, UT=20 minutes, centrifugation / decantation at 20000 rpm for 20 minutes; and 4) washing with water four times, UT and centrifugation / decantation at 20000 rpm for 20 minutes each time.

[0088] The treated EMM-23 was then dried in an oven at 60 °C overnight. The powder XRD pattern is shown in Figure 5 middle. Example 4 - Treatment of As-received EMM-23 with AlCl3·6H2O

[0089] A sample of as-received EMM-23 prepared in Example 1 was subjected to the treatments described in Example 3. The powder XRD pattern is shown in Figure 6 middle. Example 5 - Washing with water EMM-23 as received with AlCl3·6H2O

[0090] A sample of the as-received EMM-23 of Example 1 was subjected to post-synthesis alumination as described in Example 3. However, the sample was not washed with NH4OH. Instead, it was washed only six times with H2O to keep the number of washing steps similar to that in Example 3. The obtained sample was then dried in an oven at 60°C overnight. The powder XRD pattern is shown in Figure 7 middle. Example 6 - Calcined EMM-23 with AlCl3·6H2O Washing with Water

[0091] The sample of calcined EMM-23 of Example 2 was subjected to post-synthesis alumination as described in Example 3. However, the sample was not washed with NH4OH. Instead, it was washed only six times with H2O to keep the number of washing steps similar to that in Example 3. The obtained sample was then dried in an oven at 60°C overnight. The powder XRD pattern is shown in Figure 8 middle. Example 7 - Treatment of calcined EMM-23 with AlCl3·6H2O

[0092] A sample of calcined EMM-23 prepared in Example 2 was subjected to subsequent post-synthesis aluminating treatment. It was treated with 0.4 wt% AlCl3.6H2O solution at a solid-to-liquid ratio of 1:50. The mixture was stirred at 80°C for 3h at a stirring rate of 400rpm. After treatment, the sample was purified by a series of three steps (15 minutes each) of high-speed centrifugation / decanting the supernatant and redispersing the sample in water under ultrasonic treatment. The treated EMM-23 was then dried in an oven at 60°C overnight. The powder XRD pattern is shown in Fig. 9 middle. Examples 8 to 12 - Repeated treatment of calcined EMM-23 with AlCl3·6H2O

[0093] In Example 8, a sample of the treated EMM-23 prepared in Example 7 was subjected to the same treatment as described in Example 7 for a second time. In Example 9, a sample of the treated EMM-23 prepared in Example 8 was subjected to the same treatment as described in Example 7 for a third time. In Example 10, a sample of the treated EMM-23 prepared in Example 9 was subjected to the same treatment as described in Example 7 for a fourth time. In Example 11, a sample of the treated EMM-23 prepared in Example 10 was subjected to the same treatment as described in Example 7 for a fifth time. In Example 12, a sample of the treated EMM-23 prepared in Example 11 was subjected to the same treatment as described in Example 7 for a sixth time.

[0094] Fig.10 The calcined EMM-23 prepared in Example 2 and the treated EMM-23 of Examples 7 to 12 are shown. 27 AlMAS NMR spectrum. (The small peaks marked with * are spinning sidebands.) Example 13 - Treatment of calcined EMM-23 with AlNO3·9H2O

[0095] The sample of calcined EMM-23 prepared in Example 2 was subjected to subsequent post-synthesis aluminate treatment. 0.25M AlNO3.9H2O solution was treated with a solid-to-liquid ratio of 1:50. The mixture was stirred at 80°C with a stirring speed of 400rpm overnight. After treatment, the sample was purified by a series of six high-speed centrifugation / decantation supernatants and the sample was redispersed in water (15 minutes each) under ultrasonic treatment. The treated EMM-23 was then dried overnight at 60°C in an oven. Example 14 - Treatment of As-received EMM-23 with AlNO3·9H2O

[0096] A sample of the as-received EMM-23 prepared in Example 1 was subjected to the aluminating treatment described in Example 13. Example 15 - Treatment of calcined EMM-23 with (NH4)3AlF6

[0097] The sample of calcined EMM-23 prepared in Example 2 was subjected to the following post-synthesis aluminate treatment. It was treated with 0.02M (NH4)3AlF6 solution at a solid-to-liquid ratio of 1:30. The mixture was stirred overnight at 25°C with a stirring speed of 400rpm. After treatment, the sample was purified by a series of three steps of high-speed centrifugation / decantation of the supernatant and redispersion of the sample in hot water under ultrasonic treatment for 15 minutes each time. The obtained treated EMM-23 was then dried in an oven at 60°C overnight. Example 16 - Treatment of As-received EMM-23 with (NH4)3AlF6

[0098] The sample of EMM-23 prepared in Example 1 was subjected to the following post-synthesis aluminate treatment. It was treated with 0.02M (NH4)3AlF6 solution at a solid-to-liquid ratio of 1:30. The mixture was stirred for 30 minutes at room temperature under ultrasonic treatment. After treatment, the sample was purified by a series of three steps of high-speed centrifugation / decantation of the supernatant and redispersion of the sample in hot water under ultrasonic treatment for 15 minutes each time. The obtained treated EMM-23 was then dried in an oven at 60°C overnight. discuss

[0099] The Si:Al2 ratios and Bronsted acidities of the materials obtained in Examples 1 to 16 are listed in Table 7 below. Table 7 a Si:Al2 ratio obtained from ICP-MS; b not analyzed; c to be analyzed; d approximate value from EDS.

[0100] The results in Table 7 show that the calcined EMM-23 zeolite prepared in Example 2 has a Si:Al2 ratio of 375, indicating that very little Al has been incorporated into the zeolite during the crystallization process. Example 3 shows that overnight treatment of the zeolite with an aluminum salt solution results in an increase in the amount of Al in the zeolite, causing the Si:Al2 ratio to drop to 60. Example 6 shows similar results. Example 7 shows that a single 3-hour treatment also increases the Al concentration in the zeolite, but not to the same extent as the overnight treatment of Example 3.

[0101] Examples 8 to 12 show that repeated treatments lead to a gradual increase in the Al concentration in the zeolite, but the degree of increase per treatment generally decreases with the number of repetitions n from n=2 (Example 8) to n=6 (Example 12). Surprisingly, even at a total treatment time of only 6 hours (n=2, Example 8), the Si:Al2 ratio is already lower than the longer overnight treatments of Examples 3 and 6.

[0102] Examples 3, 6 and 7 to 12 illustrate the treatment of the zeolite with AlCl3.6H2O. Examples 14 and 16 illustrate the treatment of the zeolite with AlNO3.9H2O and (NH4)3AlF6, respectively.

[0103] Examples 4 and 5 show that treatment with aluminum chloride solution is also effective in increasing the aluminum content of the as-received zeolite. Examples 14 and 16 illustrate treatment of the as-received zeolite with AlNO3.9H2O and (NH4)3AlF6, respectively.

[0104] Fig.11 A shows the superimposed powder XRD patterns of calcined EMM-23 prepared in Examples 2, 3, 6 to 13, and 15. Fig.11 B shows the superimposed powder XRD patterns of the as-received EM-23 prepared in Examples 1, 4, 5, 14 and 16.

[0105] In addition to those described herein, various modifications of the present disclosure will be apparent to those skilled in the art based on the foregoing description. Such modifications are also intended to fall within the scope of the appended claims. Each reference cited in this application, including but not limited to all patents, patent applications and publications, is incorporated herein by reference in its entirety.

[0106] Additionally or alternatively, the present invention relates to:

[0107] Embodiment 1: A method for increasing the aluminum content of an EWT framework zeolite and mixtures thereof, comprising subjecting the EWT framework zeolite to a treatment comprising the following steps: a) contacting the EWT framework zeolite with an aqueous solution of an aluminum salt; and b) separating the EWT framework zeolite from the aqueous solution of the aluminum salt; and repeating the treatment such that the EWT framework zeolite is subjected to n treatment cycles in total, wherein n is a number from 2 to 10.

[0108] Embodiment 2: The method of Embodiment 1, wherein in step a), the EWT framework zeolite is contacted with the aqueous solution of aluminum salt for a duration of 1 hour to 24 hours.

[0109] Embodiment 3: The method of Embodiment 1 or 2, wherein the aluminum salt is selected from Al2(SO4)3, AlCl3, Al(NO3)3, (NH4)3AlF6 and mixtures thereof.

[0110] Embodiment 4: The method of any one of Embodiments 1 to 3, wherein in one or more of the treatment cycles, the treatment further comprises, after step b), the following step: c) washing the EWT framework zeolite with a wash liquid.

[0111] Embodiment 5: The method of Embodiment 4, wherein in at least one treatment cycle, the wash liquid is water.

[0112] Embodiment 6: The method of Embodiment 4 or 5, wherein in at least one treatment cycle, the wash liquid is an aqueous ammonium hydroxide solution.

[0113] Embodiment 7: The method of any one of Embodiments 1 to 6, wherein in one or more of the treatment cycles, the treatment further comprises the following step after step b) or step c) if present: d) drying the EWT framework zeolite.

[0114] Embodiment 8: The method of any one of Embodiments 1 to 7, wherein during step a), the contacting is carried out at a temperature of 50°C to 100°C.

[0115] Embodiment 9: The method of any one of Embodiments 1 to 8, wherein n is 3 to 6.

[0116] Embodiment 10: The method of any one of Embodiments 1 to 9, wherein the EWT framework zeolite is a calcined EWT framework zeolite.

[0117] Embodiment 11: The method of any one of Embodiments 1 to 10, wherein the EWT framework zeolite is an uncalcined EWT framework zeolite.

[0118] Embodiment 12: The method of any one of Embodiments 1 to 11, wherein the EWT framework zeolite is EMM-23.

[0119] Embodiment 13: The method of any one of Embodiments 1 to 12, wherein the EWT framework zeolite is in the form of unbound zeolite crystals.

[0120] Embodiment 14: An EWT framework zeolite produced by a method according to any of the above embodiments, wherein the Si:Al2 ratio is 70 or less.

[0121] Embodiment 15: A method of converting an organic compound into a conversion product, the method comprising the step of contacting the organic compound with the EWT framework zeolite according to Embodiment 14.

Claims

1. A method for increasing the aluminum content of an EWT framework zeolite and mixtures thereof, comprising subjecting the EWT framework zeolite to a treatment comprising the following steps: a) contacting the EWT framework zeolite with an aqueous solution of an aluminum salt; and b) separating the EWT framework zeolite from the aqueous solution of the aluminum salt; and repeating the treatment such that the EWT framework zeolite is subjected to n treatment cycles in total, wherein n is a number from 2 to 10.

2. The process of claim 1, wherein in step a), the EWT framework zeolite is contacted with an aqueous solution of an aluminum salt for a duration of 1 hour to 24 hours.

3. The method of claim 1 or claim 2, wherein the aluminum salt is selected from the group consisting of Al2(SO4)3, AlCl3, Al(NO3)3, (NH4)3AlF6 and mixtures thereof.

4. The method of any one of claims 1 to 3, wherein in one or more of the treatment cycles, the treatment further comprises the following steps after step b): c) washing the EWT framework zeolite with a washing liquid.

5. The method of claim 4, wherein in at least one treatment cycle, the wash liquid is water.

6. The method of claim 4 or claim 5, wherein in at least one treatment cycle the wash liquid is an aqueous ammonium hydroxide solution.

7. The method of any one of claims 1 to 6, wherein in one or more of the treatment cycles, the treatment further comprises the following steps after step b) or, if present, step c): d) drying the EWT framework zeolite.

8. The process of any one of claims 1 to 7, wherein during step a), the contacting is carried out at a temperature of 50°C to 100°C.

9. The method of any one of claims 1 to 8, wherein n is 3 to 6.

10. The method of any one of claims 1 to 9, wherein the EWT framework zeolite is a calcined EWT framework zeolite.

11. The method of any one of claims 1 to 10, wherein the EWT framework zeolite is an uncalcined EWT framework zeolite.

12. The method of any one of claims 1 to 11, wherein the EWT framework zeolite is EMM-23.

13. The method of any one of claims 1 to 12, wherein the EWT framework zeolite is in the form of unbound zeolite crystals.

14. An EWT framework zeolite produced by a process according to any preceding claim, wherein the Si:Al2 ratio is 70 or less.

15. A method for converting an organic compound into a conversion product, the method comprising the steps of: The organic compound is contacted with the EWT framework zeolite according to claim 14.